The identity of Pseudomystus moeschii (Boulenger, 1890), with the description of two new species of bagrid catfishes from Southeast Asia (Teleostei: Bagridae) - Ng, Heok Hee; Lim, Kelvin K.p. (Zootaxa, 2005)
The identity of the poorly known bagrid catfish Pseudomystus moeschii (Boulenger, 1890) is clarified and the species redescribed. Two new species of closely related bagrid catfishes are also described: Pseudomystus carnosus from the Way Seputih River drainage in the province of Lampung in the southern tip of Sumatra, and P. fumosus from the Pahang River drainage in eastern Peninsular Malaysia. Pseudomystus carnosus, P. fumosus and P. moeschii can be distinguished from congeners in having an enlarged posterior process of the post-temporal, presence of long hair-like epithelial projections on the skin and long tubular extensions of the sensory pores. Pseudomystus carnosus differs from the other two species in having a pointed (vs. rounded) tip of the nuchal shield, while P. fumosus differs from the other two species in having very well developed procurrent caudal rays which are sinuously curved along the anterior edges (vs. less developed procurrent caudal rays that slope evenly along the edges). A lectotype is designated for P. moeschii.